Development of machine learning models for the screening of potential HSP90 inhibitors - Khan, Mohd Imran; Park, Taehwan; Imran, Mohammad Azhar; Gowda Saralamma, Venu Venkatarame; Lee, Duk Chul; Choi, Jaehyuk; Baig, Mohammad Hassan; Dong, Jae-June (Frontiers in Molecular Biosciences, 2022)
Heat shock protein 90 (Hsp90) is a molecular chaperone playing a significant role in the folding of client proteins. This cellular protein is linked to the progression of several cancer types, including breast cancer, lung cancer, and gastrointestinal stromal tumors. Several oncogenic kinases are Hsp90 client proteins, establishing it as a prominent therapeutic strategy for cancer treatment. Studies have confirmed the inhibition of HSP90 as a striking therapeutic treatment for cancer management. In this study, we have utilized machine learning and different in silico approaches to screen the KCB database to identify the potential HSP90 inhibitor. Further evaluation of these inhibitors on various cancer cell lines showed favorable inhibitory activity. These inhibitors could serve as a basis for developing effective HSP90 inhibitors further.